(untitled) (World Bulletin of Management and Law, 2022)
This study aimed to clarify the relationship between the dimensions of social responsibility (i.e., economic, human, legal, and ethical) on the quality of health services with its dimensions (safety, reliability, continuity, efficiency and effectiveness, technical and material capabilities) at governmental hospitals in the city of Tikrit. The researcher depended on the descriptive analytical approach; the questionnaire was obtained to collect data from its sources, which were prepared specifically for this study, relying on scientific references, and the study sample was based on the comprehensive sample method. The results of the statistical analysis revealed a positive and statistically significant impact of the dimensions of social responsibility on the dimensions of the quality of health services. The study recommended enhancing the interest of government health institutions in social responsibility and the quality of health services, and working on continuous improvement to improve health services provided by governmental health institutions, and strengthening government health institutions’ social responsibility towards the community in which they operate.